Argasid and ixodid systematics: Implications for soft tick evolution and systematics, with a new argasid species list - (:unkn) unknown (My University, 2019)
The systematics of the genera and subgenera within the soft tick family Argasidae is not adequately resolved. Different classification schemes, reflecting diverse schools of scientific thought that elevated or downgraded groups to genera or subgenera, have been proposed. In the most recent classification scheme, Argas and Ornithodoros are paraphyletic and the placement of various subgenera remains uncertain because molecular data are lacking. Thus, reclassification of the Argasidae is required. This will enable an understanding of soft tick systematics within an evolutionary context. This study addressed that knowledge gap using mitochondrial genome and nuclear (18S and 28S ribosomal RNA) sequence data for representatives of the subgenera Alectorobius, Argas, Chiropterargas, Ogadenus, Ornamentum, Ornithodoros, Navis (subgen. nov.), Pavlovskyella, Persicargas, Proknekalia, Reticulinasus and Secretargas, from the Afrotropical, Nearctic and Palearctic regions. Hard tick species (Ixodidae) and a new representative of Nuttalliella namaqua (Nuttalliellidae), were also se-quenced with a total of 83 whole mitochondrial genomes, 18S rRNA and 28S rRNA genes generated. The study confirmed the utility of next-generation sequencing to retrieve systematic markers. Paraphyly of Argas and Ornithodoros was resolved by systematic analysis and a new species list is proposed. This corresponds broadly with the morphological cladistic analysis of Klompen and Oliver (1993). Estimation of divergence times using molecular dating allowed dissection of phylogeographic patterns for argasid evolution. The discovery of cryptic species in the subgenera Chiropterargas, Ogadenus and Ornithodoros, suggests that cryptic speciation is common within the Argasidae. Cryptic speciation has implications for past biological studies of soft ticks. These are discussed in particular for the Ornithodoros (Ornithodoros) moubata and Ornithodoros (Ornithodoros) savignyi groups.
Keywords: African Research